Impact of the urban atmospheric environment on otolaryngologic disease outpatient visits in Lanzhou, China - Juanli Li; Chengyu Feng; Xuanlong Ma; Duo Wu (Scientific Reports)
Abstract Lanzhou, an industrial city in northwestern China, is prone to air pollution due to its unique valley basin topography. The incidence of otolaryngologic diseases is closely related to the air quality. Based on air-quality data and outpatient data from an otolaryngology clinic within a hospital in Lanzhou during 2014‒2022, we analyzed the statistical relationships between the concentrations of six common air pollutants and the number of outpatient visits for common otolaryngologic inflammatory diseases using a generalized additive model. We used the results to discuss the potential role of urban airborne pollen in contributing to allergic rhinitis, and we also examined the variability of the relationship between air pollutants and otolaryngologic diseases under anthropogenic interventions using periods before and during the COVID-19 outbreak. Rising concentrations of CO, NO2, PM2.5, PM10, and SO2 in Lanzhou led to an increase in the number of outpatient visits for otolaryngologic inflammatory diseases, and the impact patterns were different for different genders and different diseases. In terms of gender, CO, NO2, and SO2 had a significantly greater impact on the number of visits for otolaryngologic inflammatory disease for males than for females, while PM2.5 and PM10 had a more significant impact on the female population. The number of outpatient visits for acute otitis media and allergic rhinitis also increased with increasing concentrations of the above five pollutants, while airborne pollen was an important trigger for high incidences of allergic rhinitis in July and August. In addition, during the period of lockdown and control due to the COVID-19 pandemic, there was a decrease in the relative risk of the five aforementioned pollutants with respect to the occurrence of inflammatory otolaryngologic disorders. The effect of these pollutants on such disorders was reduced compared with that observed during the pre-pandemic period, indicating that effective air pollution control is an important measure that can be implemented to reduce the occurrence of otolaryngologic inflammatory diseases and protect residents. This study reveals the occurrence pattern of otolaryngologic diseases and their relationships with air pollutants in Lanzhou, which is important for the prevention of otolaryngologic diseases and the formulation of air pollution control strategies.